A co-designed, community-based intensive health behavior intervention promotes participation and engagement in youth with risk factors for type 2 diabetes - Pike, Julie M.; Haberlin-Pittz, Kathryn M.; Alharbi, Basmah S.; Perkins, Susan M.; Hannon, Tamara S. (Frontiers in Clinical Diabetes and Healthcare, 2023)
Background Obesity among youth (children and adolescents) is associated with increased risk for youth-onset type 2 diabetes. Lifestyle change can delay or prevent the development of type 2 diabetes, yet real-world implementation of health behavior recommendations is challenging. We previously engaged youth with risk factors for type 2 diabetes, their caregivers, and professionals in a human-centered design study to co-design a lifestyle change program. Here we report the outcomes for this 16-week co-designed lifestyle change program for youth at risk for T2D and their caregivers. Research design and methods This single-arm family-based cohort study included youth aged 7-18 years, with BMI ≥85th percentile (overweight or obese) and at least one additional risk factor for type 2 diabetes, and their caregivers. Clinical (BMI, HbA1c), self-reported physical activity, and quality of life outcomes were evaluated at baseline (B), post-intervention (M4), and 1 year (M12) following the intervention. Results Seventy-eight youth (mean age 12.4 ± 2.7y, 67% female, 37.8% white) and 65 caregivers were included in the data analysis. Youth baseline BMI z-scores (2.26 ± 0.47) and HbA1c (5.3 ± 0.3) were unchanged at follow up time points [BMI z-scores M4 (2.25 ± 0.52), M12 (2.16 ± 0.58), p-value 0.46], [HbA1c M4 (5.3 ± 0.3), M12 (5.2 ± 0.3), p-value (0.04)]. Youth reported increased physical activity at M4 (p = 0.004), but not at M12. Youth quality of life scores increased at M12 (p=0.01). Families who attended at least one session (n=41) attended an average of 9 out of 16 sessions, and 37 percent of families attended 13 or more sessions. Conclusion A co-designed, community-based lifestyle intervention promotes increased physical activity, improved quality of life, maintenance of BMI z-scores and HbA1c, and engagement in youth with risk factors for T2D.